乌尔姆设计学院：20 世纪50 至60 年代联邦德国工业设计的训练中心 - The Ulm School of Design: A Training Center for Industrial Design in the Federal Republic of Germany in the 1950/60s - Seng, Eva- Maria (Zhuangshi 7)

包豪斯：20 世纪艺术、设计和建筑领域最具影响力的艺术学院 - Bauhaus: The Most Influential Art School in the Field of Arts, Design and Architecture in the 20th Century - Seng, Eva- Maria (Zhuangshi 11)

- “德国制造”——德意志制造联盟：20 世纪早期的德国工业设计、建筑设计与艺术院校改革 - ‘Made in Germany’- The German Werkbund: Industrial Design, Architecture and Art School Reform in the Early 20th Century - Seng, Eva- Maria (Zhuangshi 6)

The Museum - Seng, Eva- Maria (Tsinghua Art Museum TAM 11)

Geometrische Muster zwischen frühneuzeitlicher Utopie und russischer Avantgarde - Seng, Eva- Maria; Saage, Richard (Bauen mit Sinn. Schritte zu einer Philosophie der Architektur)

Kandidatur zum Bauhüttenwesen Die internationale für das immaterielle Kulturerbe der UNESCO - Seng, Eva- Maria („Genius loci“. Dombaumeistertagung Paderborn 23.-29. September 2018)

Kinder als Forscher in eigener und gemeinsamer Sache – ein Weg zur Partizipation? Ein kinderrechtebasierter didaktischer Ansatz und dessen Relevanz aus der Perspektive von Grundschulkindern - Hüpping, Birgit; Büker, Petra (Pädagogischer Blick)

Combining Children's Participation Rights in Research with Professionalisation of Educators and Teachers – Critical Analysis of a Transition Study Design - Büker, Petra (The Routledge International Handbook of Young Children’s Rights)

Kompetenzerwerb im Lese- und Literaturunterricht der Grundschule - Büker, Petra; Vorst, Claudia (Lese- und Literaturunterricht)
stark überarbeitete Auflage. (Deutschunterricht in Theorie und Praxis, Bd. 11/2). Baltmannsweiler: Schneider Verlag.

Partizipation von Kindergarten- und Grundschulkindern an Übergangsgestaltung, Übergangsforschung und am Transfer in optimierte Praxis: Erfahrungen aus der Kinderbefragungsstudie „buddY“. - Büker, Petra (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Children’s voices as a bridge between educators in kindergarten and teachers in primary school: Potential of children’s perspectives to support professional development - Büker, Petra; Höke, Julia (Listening to children’s advice about starting school and school age care. EECERA Book Series: Towards an Ethical Praxis in Early Childhood: From Research into Practice)

Perspektiven des Transfers von Forschungsbefunden im Übergang Kindergarten-Grundschule - Büker, Petra; Müller, Ulrike Beate; Seifert, Anja; Arndt, Petra; Carle, Ursula; Graf, Ulrike; Kieferle, Christa; Kordulla, Agnes; Sturmhöfel, Nicole; Wehner, Franziska (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen

Grundthemen der Literaturwissenschaft: Literarische Institutionen

Zersetzung. Automatismen und Strukturauflösung
Erscheinungsjahr in Klammern: 2018

Die Explosion der Bilder im Kopf oder: „Les beaux livres sont écrits dans une sorte de langue étrangère.“ - Eke, Norbert Otto (Werner Fritsch: Faust Sonnengesang II und III. Materialien)

„Es ist nur eine Probe.“ George Taboris ‚musikalisches Opfer‘ „Die Goldberg-Variationen“ - Eke, Norbert Otto (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen biblischer Texte - Eke, Norbert Otto; Strotmann, Angelika (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Literarische Institutionen - Eke, Norbert Otto; Elit, Stefan (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Historischer Abriss: Aufklärung bis Gegenwart - Eke, Norbert Otto (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Zersetzung(en) dramatischer Ordnung: Marlene Streeruwitz und Rainald Goetz - Eke, Norbert Otto (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Zersetzung. Automatismen und Strukturauflösung - Eke, Norbert Otto; Hohlweck, Patrick (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Success Factors for the Consolidation and Anchoring of Digitalisation Projects - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Strategies Beyond Borders – Transforming Higher Education in a Digital Age. Book of Abstracts)

Digitalisierungsstrategien auf dem Prüfstand – eine empirische Untersuchung auf Basis der Grounded-Theory-Methodologie an deutschen Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Teilhabe in der digitalen Bildungswelt)

Inwiefern verbessert bilingualer Sachfachunterricht die Englischkompetenzen von Schülerinnen und Schülern? - Rumlich, Dominik (Die große Frage)

Freies Format 9: Nachwuchscafé - Juchem-Grundmann, Constanze; Matz, Frauke; Rumlich, Dominik (Sprachen lernen integriert: global, regional, lokal. Dokumentation zum 27. Kongress für Fremdsprachendidaktik der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF). Jena, 27.-30. September 2017)

Kohärenz im Englischstudium für die Primarstufe: Das Lehr-Lern-Konzept des Wuppertaler Projekts EULE - Diehr, Bärbel; Becker, Annette; Breul, Carsten; Frisch, Stefanie; Kastens, Claudia; Rumlich, Dominik (Kohärenz in der Lehrerbildung)

Requirements Engineering in OTF-Computing - Bäumer, Frederik Simon; Geierhos, Michaela (encyclopedia.pub)
Keywords: OTF Computing; Natural Language Processing; Requirements Engineering

Supporting learning at work in an era of digitalization of work - Harteis, Christian (Work-based learning as a pathway to competence-based education)

Natural Language Processing in OTF Computing: Challenges and the Need for Interactive Approaches - Bäumer, Frederik Simon; Kersting, Joschka; Geierhos, Michaela (Computers)
The vision of On-the-Fly (OTF) Computing is to compose and provide software services ad hoc, based on requirement descriptions in natural language. Since non-technical users write their software requirements themselves and in unrestricted natural language, deficits occur such as inaccuracy and incompleteness. These deficits are usually met by natural language processing methods, which have to face special challenges in OTF Computing because maximum automation is the goal. In this paper, we present current automatic approaches for solving inaccuracies and incompletenesses in natural language requirement descriptions and elaborate open challenges. In particular, we will discuss the necessity of domain-specific resources and show why, despite far-reaching automation, an intelligent and guided integration of end users into the compensation process is required. In this context, we present our idea of a chat bot that integrates users into the compensation process depending on the given circumstances.
Keywords: Inaccuracy Detection; Natural Language Software Requirements; Chat Bot

UPB-Annotate: Ein maßgeschneidertes Toolkit für historische Texte - Seemann, Nina; Merten, Marie-Luis (DHd 2019 Digital Humanities: multimedial & multimodal. Konferenzabstracts)

Potentielle Privatsphäreverletzungen aufdecken und automatisiert sichtbar machen - Bäumer, Frederik Simon; Buff, Bianca; Geierhos, Michaela (DHd 2019 Digital Humanities: multimedial & multimodal. Konferenzabstracts)

In Reviews We Trust: But Should We? Experiences with Physician Review Websites - Kersting, Joschka; Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 4th International Conference on Internet of Things, Big Data and Security)
The ability to openly evaluate products, locations and services is an achievement of the Web 2.0. It has never been easier to inform oneself about the quality of products or services and possible alternatives. Forming one’s own opinion based on the impressions of other people can lead to better experiences. However, this presupposes trust in one’s fellows as well as in the quality of the review platforms. In previous work on physician reviews and the corresponding websites, it was observed that there occurs faulty behavior by some reviewers and there were noteworthy differences in the technical implementation of the portals and in the efforts of site operators to maintain high quality reviews. These experiences raise new questions regarding what trust means on review platforms, how trust arises and how easily it can be destroyed.
Keywords: Trust; Physician Reviews; Network Analysis

Victorian Ideologies in Contemporary British Cultures

(New?) Masculinities in Nineteenth-Century Sensation Fiction and Contemporary Black British Fiction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Introduction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Victorian Ideologies in Contemporary British Cultures

Digitaler Wandel als strategischer Transformationsprozess – Zum allgemeinen und hochschulspezifischen Verständnis der Digitalisierung - Oevel, Gudrun; Graf-Schlattmann, Marcel; Meister, Dorothee M.; Wilde, Melanie

How to Boost Customer Relationship Management via Web Mining Benefiting from the Glass Customer’s Openness - Bäumer, Frederik Simon; Buff, Bianca (Proceedings of the 8th International Conference on Data Science, Technology and Applications)

Requirements Engineering im OTF-Computing: Informationsextraktion und Unvollständigkeitskompensation mittels domänenspezifischer Wissensbasis - Friesen, Edwin

Finnish and German student teachers’ motivations for choosing teaching as a career. The first application of the FIT-Choice scale in Finland - Goller, Michael; Ursin, Jani; Vähäsantanen, Katja; Festner, Dagmar; Harteis, Christian (Teaching and Teacher Education)

Logik im Logischen Empirismus - Peckhaus, Volker (Der Wiener Kreis – Aktualität in Wissenschaft, Literatur, Architektur und Kunst)

Konstruktionen des Terrors. Zur Hassrede in den Romanen Jenseits von Deutschland von George Tenner und Das dunkle Schiff von Sherko Fatah - Willeke, Stephanie (Hass/Literatur. Literatur- und kulturwissenschaftliche Beiträge zu einer Theorie- und Diskursgeschichte)

„So kommt doch alles noch zum Happy End.“ Sammy Gronemanns zionistische Komödie Der Prozess um des Esels Schatten - Willeke, Stephanie (Zwischen den Sprachen – Mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

Der eingehegte Terrorist? Dorothea Dieckmanns Guantánamo - Willeke, Stephanie (Das Politische in der Literatur der Gegenwart)

Portfolioarbeit als Professionalisierungsgelegenheit - Ballweg, Sandra (Portfolioarbeit im Kontext von Sprachenunterricht. Neue internationale Entwicklungen)

Das Verhältnis zwischen Fremdsprachenerwerbsforschung und Fremdsprachenunterricht - Einführung in das Themenfeld - Ballweg, Sandra; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Theorien und Hypothesen für den L2-Erwerb - Einführung in das Themenfeld - Ballweg, Sandra; Introna, Silvia; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Wille, Matthias, "Gottlob Frege. Begriffsschrift, eine der arithmetischen nachgebildete Formelsprache des reinen Denkens", Springer Spektrum: Berlin 2018 (Klassische Texte der Wissenschaft) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Honerkamp, Josef, "Denken in Strukturen und seine Geschichte. Von der Kraft des mathematischen Beweises", Springer: Berlin 2018 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)